Facile One-Pot Fischer–Suzuki–Knoevenagel Microwave-Assisted Synthesis of Fluorescent 5-Aryl-2-Styryl-3H-Indoles - Martynas Rojus Bartkus; Neringa Kleizienė; Aurimas Bieliauskas; Algirdas Šačkus (Molecules)
In this study, novel fluorescent 5-aryl-2-styryl-3H-indole derivatives were efficiently synthesized from 4-bromophenylhydrazine hydrochloride using the microwave-accelerated one-pot technique, which includes Fischer synthesis, Suzuki cross-coupling, and Knoevenagel condensation. The structural assignments of the synthesized compounds were based on 1H, 13C, 15N, and 19F NMR; IR spectroscopy; and HRMS spectral data. The optical properties of the newly obtained styryl-indole dyes were studied using UV-vis and fluorescence spectroscopy, which clearly demonstrated that the derivatives substituted with electron-donating or -withdrawing groups exhibited varying emission shifts and quantum yields ranging from negligible to high.